IMPORTANCE OF DISTANCE EDUCATION TODAY - Baltayeva AnadjanTadjibayevna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: In this article, one of the advanced foreign experiences ineducation today is the integrative organization of education, the creation of a newpsychological process, a new structure of activity through integration, any lowerlevel of interdisciplinary communication, the study being studied. among certaindidactic units within the scope of their subjects, the content of their study and themain areas of distance education and the use of distance education in education arediscussed.